A preliminary study on WAQF for hypermarkets: a new dimension for the WAQF fund - Bin Mohd Nor, Mohd Nazri (International Journal of Engineering and Technology, 2018)
The development of retail business in Malaysia has evolved year by year. It is due to many factors including the types and business rules, the goods sold, business locations, the external structure (building) and interior decoration. The country's strong economic growth, political stability and the purchasing power of incomes and a growing population have greatly contributed to the development of retail business activities in our country. In addition to the local grocery store, there are also foreign retailers who are keen to invest here due to the factors described above, including retailers that create business concept hypermarkets. This paper explores the potentials of utilizing a waqf fund in a high impact business in particular the hypermarket which can steer and boost the Ummahâ€™s economy. As the authorized body for Waqf affairs in Malaysia, it is proposed that the Islamic religious council, as well as other parties, be involved in this effort.Â